Pengaruh Orientasi Inovasi Terhadap Kinerja Usaha Pada Pelaku Usaha Mikro Kecil dan Menengah (UMKM) di Kota Bandung - Putra, Bintang Surya Putra; Putri, Mediany Kriseka Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to find out how much innovation orientation affects business performance on MSME actors in the city of Bandung from various business sectors. The dimensions of innovation orientation used include product innovation, process innovation, marketing innovation, and organizational innovation. The method used in this study is descriptive quantitative. The questionnaire was distributed to 385 MSME actors in the city of Bandung, then statistical tests were carried out using simple and multiple regression analysis using IBM SPSS. The results of this study are that simultaneously the innovation orientation variable has a significant effect on business performance with an influence value of 63.3%. Partially, the dimension of innovation orientation (product innovation, process innovation, marketing innovation, organizational innovation) has an influence on business performance in MSME actors in the city of Bandung, process innovation is the most influential dimension with a coefficient value of 0.362. The researcher suggested that the next researcher can use other variables that can affect business performance, such as entrepreneurial orientation.